Asymmetric stem-loop–mediated isothermal amplification of nucleic acids for DNA diagnostic assays by simple modification of canonical PCR primers - Mao, Rui; Wu, Xinyao; Miao, Qing; Cai, Ting (Frontiers in Bioengineering and Biotechnology, 2022)
Nucleic acids-based assays have been widely applied in clinical diagnostics, food safety monitoring, and molecular biology with the merits of accuracy, rapid and sensitivity. Loop-mediated isothermal amplification (LAMP) is a well-established nucleic acids amplification method and has gained recognition and been developed for clinical applications in resource limited areas. However, the needs for specifically designed primer sets and non-specific amplification pose challenges for development of LAMP-based detection methods. Here, a promoted method, termed asymmetric stem-loop mediated isothermal amplification (ASLAMP) by simple modification of canonical PCR primers, was developed to attempt to overcome those drawbacks. The two primers in ASLAMP reaction are easily designed by adding a stem-loop part to one canonical PCR primer at 5’-ends and adding the same primer to the counter canonical PCR primer at 5’-ends. The ASLAMP method was demonstrated in detecting H1N1 gene fragment with merits of short target sequence, simple primer design and high amplification efficiency. In addition, the ASLAMP method showed similar amplification efficacy compared with LAMP targeting at same H1N1 gene sequence. Furthermore, Shigella detection monitored by real-time fluorescence and endpoint colorimetric approaches were taken as examples for evaluation of practical application of ASLAMP method, both offered 100% sensitivity and specificity. In conclusion, the novel ASLAMP method with simplicity, efficiency and rapidity has shown its great potential for establishment of nucleic acids isothermal amplification in point of care application.